2023
DOI: 10.1097/prs.0000000000010801
|View full text |Cite
|
Sign up to set email alerts
|

Early Complications after Prepectoral Tissue Expander Placement in Breast Reconstruction with and without Acellular Dermal Matrix

Abstract: Background: Prepectoral breast reconstruction has become popularized with the concurrent use of acellular dermal matrix (ADM). The authors sought to compare 3-month postoperative complication rates and explantation rates for first-stage, tissue-expander-based, prepectoral breast reconstruction with and without the use of ADM. Methods: A single-institution retrospective chart review was performed to identify consecutive patients undergoing prepectoral tissue-expander-based breast reconstruction from August of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…It has been demonstrated that acellular matrices undergo neo-vascularization and recellularization by host cells ( 19 - 21 ). In breast reconstruction, ADMs are used to enhance skin coverage, particularly after the placement of a silicone implant or tissue expander ( 4 , 22 ). Another goal is to reduce the risk of capsule contracture, a significant complication of implant-based surgeries, leading to a substantial decrease in the long-term cosmetic result ( 23 ).…”
Section: Literature Review Of Tissue- and Bio-engineering Approaches ...mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that acellular matrices undergo neo-vascularization and recellularization by host cells ( 19 - 21 ). In breast reconstruction, ADMs are used to enhance skin coverage, particularly after the placement of a silicone implant or tissue expander ( 4 , 22 ). Another goal is to reduce the risk of capsule contracture, a significant complication of implant-based surgeries, leading to a substantial decrease in the long-term cosmetic result ( 23 ).…”
Section: Literature Review Of Tissue- and Bio-engineering Approaches ...mentioning
confidence: 99%
“…Another goal is to reduce the risk of capsule contracture, a significant complication of implant-based surgeries, leading to a substantial decrease in the long-term cosmetic result ( 23 ). Some authors have described the risks associated with using ADMs, including infection rates, skin blisters, and overall complications ( 22 , 24 ). Some concerns were initially raised related to red breast syndromes found to be linked to ADMs by reconstructive surgeons ( 25 , 26 ).…”
Section: Literature Review Of Tissue- and Bio-engineering Approaches ...mentioning
confidence: 99%
“…However, it is important to note that there is still a need for larger and higher-quality studies that compare the technique of prepectoral breast reconstruction both with and without the use of ADMs in order to draw any definite conclusions [20].The latest research on prepectoral breast reconstruction without meshes is illustrated in Table 2. PPBR with and without mesh assistance found no difference between groups in hematoma, infection, or explanation rates, whereas capsular contracture and seroma rates were higher in the no-mesh cohort Piers et al [45] 2023 Found no significant differences in outcomes between prepectoral breast reconstruction with and without acellular dermal matrix Chen et al [46] 2023 PPBR with no biosynthetic scaffold had the lowest rates of capsular contracture and may provide the most optimal balance between economic and clinical considerations in implant-based reconstruction…”
Section: Prepectoral Breast Reconstruction Without Meshesmentioning
confidence: 99%